Quick Evaluation Study on Fourteen (14) Major Development Programmes in Jehanabad District of Bihar State affected by Left Wing Extremism (LWE) - Planning Commission (Planning Commission, 2011)
Planning Commission has a strong conviction that Left-Wing Extremism (LWE) in the country is not a mere law and order problem, instead, the socio-economic dimensions of LWE are crucial and there is an urgent need to appropriately address them. In order to get an in-depth understanding of the overall development scenario, AMS was entrusted by the Planning Commission to conduct a quick evaluation of the major development programs in 5 Left Wing Extremism (LWE) affected districts of Bihar, namely, Arwal, Aurangabad, Gaya, Jamui and Jehanabad.
Programme Evaluation Organisation, Planning Commission, Government of India